ENHANCEMENT OF WALL INSULATION AND REDUCTION OF HEAT GAIN IN BUILDINGS USING A NEW MODEL BRICK: LITERATURE REVIEW (Spectrum Journal of Innovation, Reforms and Development, 2026)
This paper reviews recent advancements in insulating brick technologies aimed at reducing heat gain through building walls, focusing on hollow, multi-chambered, and material-enhanced brick configurations. Given the high contribution of walls to thermal loads in hot climates, integrating insulation directly within brick units emerges as a practical and energy-efficient solution. The study highlights both numerical and experimental investigations validating the role of geometry optimization, phase change materials (PCMs), and waste-derived additives in improving thermal resistance. The analysis also considers the environmental and economic benefits of sustainable materials. Findings suggest that the integration of advanced insulation strategies within brick structures significantly enhances building energy performance, making them suitable for future climate-resilient construction.